The merging of reciprocal teaching and 5e instructional model: a conceptual framework - Ting Pick Dew; Suyansah Swanto; Vincent Pang (Human Resource Management Academic Research Society (HRMARS), 2021)
Reading entails cognitive and linguistics competencies, from basic decoding to complex comprehension structure that includes integration of one’s knowledge of the world, thus is the main building blocks of learning and knowledge. However, reading is more than just the ability to recognize words and decode information. Successful reading requires an active interaction between the reader’s interpretation of the printed information, critical evaluation of the message and application of the newfound knowledge. This requirement necessitates the need to activate reading comprehension strategies that facilitate the representational construction of a text. This conceptual paper highlights a framework that allows the scaffolding and meaning construction to be performed through modelling, guiding and application of reading strategies. The integration of reciprocal teaching which is an instructional technique that builds on modelling and scaffolding four reading strategies, into the five phases of the inquiry-based learning cycle might impel reluctant readers to regain interest in reading by learning the suggested strategies in the predetermined phases.